Global homophobia states, movements, and the politics of oppression - Weiss, Meredith L.; Bosia, Michael J. (University of Illinois Press, 2013)
While homophobia is commonly characterized as individual and personal prejudice, this collection of essays instead explores homophobia as a transnational political phenomenon. Contributors theorize homophobia as a distinct configuration of repressive state-sponsored policies and practices with their own causes, explanations, and effects on how sexualities are understood and experienced in a range of national contexts.